2013
DOI: 10.1186/1471-2164-14-64
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and contrast of genes and biological pathways responding to Marek’s disease virus infection using allele-specific expression and differential expression in broiler and layer chickens

Abstract: BackgroundMarek’s disease (MD) is a commercially important neoplastic disease of chickens caused by the Marek’s disease virus (MDV), a naturally occurring oncogenic alphaherpesvirus. Enhancing MD genetic resistance is desirable to augment current vaccines and other MD control measures. High throughput sequencing was used to profile splenic transcriptomes from individual F1 progeny infected with MDV at 4 days of age from both outbred broilers (meat-type) and inbred layer (egg-type) chicken lines that differed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…Our group has previously demonstrated that Jak-STAT is an important cellular pathway involved in genetic basis of MD resistance [20,30]. Similarly, we also noted that genes in Jak-STAT pathway are transcriptionally up-regulated in susceptible line 7 and not in the resistant line 6.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Our group has previously demonstrated that Jak-STAT is an important cellular pathway involved in genetic basis of MD resistance [20,30]. Similarly, we also noted that genes in Jak-STAT pathway are transcriptionally up-regulated in susceptible line 7 and not in the resistant line 6.…”
Section: Discussionsupporting
confidence: 70%
“…However, it is worth noting transcript profiling using spleens and other organs suffers from the potential confounding influence of differences in cellular composition and reagents to properly quantify each cell subtype are limiting in chicken. Thus, the high degree of overlap between our current results, which utilized cultured cells from defined chicken lines, and those from our other studies that used actual birds [11,12,20,30] for the identification of critical pathways suggests that CEF are reasonable models. This agreement also suggests an important contribution of innate immunity towards MD genetic resistance.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Comprehensive analysis of AIV-infected lung tissue suggested that several microRNA (miRNAs) and mRNAs were likely to be involved in regulating the host response (Wang et al, 2012). Allele-specific expression (SNPs, genes and pathways) that was associated with transcriptional response to Marek´s disease virus (MDV) infection was identified to underlay genetic basis for disease resistance to MDV infection in both broilers and layers (Perumbakkam et al, 2013). Gene expression patterns of normal and duck hepatitis A virus genotype C (DHAV-C) infected duck livers were explored and compared, and new insights into the molecular mechanism of host-DHAV-C interaction were provided .…”
Section: Transcriptomics and Virus-host Interactionmentioning
confidence: 99%